Problems of Interior Troops in border areas in the reason of exceptional circumstances that might prompt an internal armed conflict and the overall approach of solution - Sutyushev Т. А.; Chuhlatuy, A. V. (Honor and Law, 2019)
To problems of Interior Troops associated with the need to respond to a wide range of threats to internal security in a departmental isolation forces the security sector and defense, as well as offer a general approach for their solution are given.